A hybrid authentication protocol for LTE/LTE-A networks - Vu, Hoang Anh (2016)
Wireless technology has revolutionized the way people work, communicate and entertain. The constant evolution of mobile devices enables us to transfer or access practically anything via the wireless network. Now that people are using their smartphones or tablets to perform more complicated transactions, ensuring the security of these actions has become more critical. Information leakage in a money transfer transaction or private email exchange can cause unimaginable financial and confidential information losses. Therefore, protecting information exchanged via wireless network is one of the top priorities in network design nowadays. LTE (Long Term Evolution) is one of the most common 4th generation cellular networks which can support high data transmission rate and wide coverage. However, LTE networks still have security vulnerabilities in terms of network architecture, access and handover procedure, media and machine type mechanisms. This project focuses on the security of LTE access procedure. Major weaknesses of LTE authentication process are identified at the beginning phase of this project. Multiple existing solutions are reviewed and analyzed based on performance and security level. A new approach to address the identified vulnerabilities – the HEPS (Hybrid Evolved Packet System) protocol, is discovered and verified. The proposed HEPS protocol can not only solve the security issues of LTE access procedure, but also optimize the performance of the process. The protocol has been verified logically (using BAN logic) and systematically (using AVISPA tool). The security and performance of the HEPS protocol are also compared to some current solutions. The result of this project is useful in addressing the security vulnerabilities of LTE authentication process.